Maximization of furanic compounds formation by dehydration and hydrogenation of xylose in one step over SO3-H functionalized H-beta catalyst in alcohol media - Gupta, Anshita; Nandanwar, Sachin U.; Niphadkar, Prashant; Simakova, Irina; Bokade, Vijay (Biomass & Bioenergy, 2020)
Furanic compounds such as furfural (FUR); furfuryl alcohol (F. Alc) are important renewable platform chemicals can be used as such or further convert for preparation of other value added products such as Levulinic acid (LA), Alkyl Levulinates, 2-Methyltetrahydrofuran (MTHF), and Tetrahydrofuran (THF) etc. Sulfonated H-beta zeolite was successfully prepared and used for the synthesis of furanic compounds especially FUR and F. Alc from c-xylose in one step using isopropanol as alcohol media. Prepared catalyst was well characterized by powder X-ray diffraction (XRD), scanning electron microscopy (SEM), BET, NH3-Temperature programmed desorption (TPD) and carbon-hydrogen-nitrogen-sulfur analysis (CHNS). It was found the total acid amount was increased with increase in sulfur loading which confirmed the sulfonic acid group (SO3-H) was successfully grafted onto zeolite structure. 3 wt% H-beta-SO3-H catalyst with optimized reaction parameters of 150 degrees C, 7 h, 25 wt% catalyst loading was tuned to get the highest furanic compound yield of 88.5% (FUR 76.8% + F.Alc 11.7%).The reusability study confirmed that there was a marginal drop of similar to 25% after 3 recycle runs.
Keywords: furfural; Furfuryl alcohol; H-beta; isopropanol; sulfonated zeolite; Xylose

Milder operating parameters for one-step conversion of fructose to levulinic acid over sulfonated H-β zeolite in aqueous media - Bisen, Swapneel K.; Niphadkar, Prashant S.; Nandanwar, Sachin U.; Simakova, Irina; Bokade, Vijay V. (Environmental Progress & Sustainable Energy, 2021)
Abstract The sulfonated H-β zeolite was successfully prepared and used for the synthesis of levulinic acid (LA) from D-fructose. The catalyst was characterized by powder X-ray diffraction, Fourier transform infrared spectroscopy, scanning electron microscope, N2 physisorption, NH3-temperature programmed desorption and carbon–hydrogen–nitrogen–sulfur analysis. The total acid amount is increased with increase in sulfur loading, confirmed that the sulfonic acid group (SO3-H) is successfully grafted onto zeolite structure. The various parameters such as different amount of sulfur loading, reaction temperature, time, catalyst loading was studied for selective production of LA. The catalytic activity of sulfonated H-β (S-β) zeolite was found to be efficient for synthesis of LA from D-fructose in aqueous media. Maximum LA yield of 43.5 mol%, low HMF yield (<1%) with 98.15% fructose conversion was obtained with 3% S-β catalyst at 160°C for 7 hr. The catalyst was reusable for minimum three times by H2O2 regeneration. This study provides the new zeolitic catalyst for the efficient production of LA at shorter reaction time (7 hr) and low catalyst to substrate ratio (0.7:1).
Keywords: conversion; D-fructose; H-β; HMF; levulinic acid; sulfonated zeolite; yield

Milder operating parameters for one-step conversion of fructose to levulinic acid over sulfonated H-beta zeolite in aqueous media - Bisen, Swapneel K.; Niphadkar, Prashant S.; Nandanwar, Sachin U.; Simakova, Irina; Bokade, Vijay V. (Environmental Progress & Sustainable Energy, 2021)
The sulfonated H-beta zeolite was successfully prepared and used for the synthesis of levulinic acid (LA) fromD-fructose. The catalyst was characterized by powder X-ray diffraction, Fourier transform infrared spectroscopy, scanning electron microscope, N-2 physisorption, NH3-temperature programmed desorption and carbon-hydrogen-nitrogen-sulfur analysis. The total acid amount is increased with increase in sulfur loading, confirmed that the sulfonic acid group (SO3-H) is successfully grafted onto zeolite structure. The various parameters such as different amount of sulfur loading, reaction temperature, time, catalyst loading was studied for selective production of LA. The catalytic activity of sulfonated H-beta (S-beta) zeolite was found to be efficient for synthesis of LA from D-fructose in aqueous media. Maximum LA yield of 43.5 mol%, low HMF yield (<1%) with 98.15% fructose conversion was obtained with 3% S-beta catalyst at 160 degrees C for 7 hr. The catalyst was reusable for minimum three times by H2O2 regeneration. This study provides the new zeolitic catalyst for the efficient production of LA at shorter reaction time (7 hr) and low catalyst to substrate ratio (0.7:1).
Keywords: conversion; D-fructose; H-beta; HMF; levulinic acid; sulfonated zeolite; yield

One-pot cascade conversion of renewable furfural to levulinic acid over a bifunctional H3PW12O40SiO2 catalyst in the absence of external H-2 - Nandiwale, Kakasaheb Y.; Vishwakarma, Mona; Rathod, Simmy; Simakova, Irina; Bokade, Vijay V. (Energy & Fuels, 2021)
The conversion of biomass-derived furfural (FUR) to levulinic acid (LA), a versatile platform chemical, involves catalytic hydrogenation of FUR followed by acid hydrolysis to LA. However, this two-step process demands expensive separation and purification of the furfuryl alcohol (FAL) intermediate. Herein, we demonstrate an ingenious catalytic strategy for the one-pot cascade conversion of FUR to LA over a bifunctional catalyst without using pure external H-2. Isopropyl alcohol (IPA) served a dual role as a hydrogen donor and solvent while inhibiting the side reactions. Catalysts with a tunable surface area and acidity were synthesized by impregnating different percentages of H3PW12O40 (heteropolyacid) over a SiO2 support. The bifunctionality of the H3PW12O40/SiO2 catalyst is ascribed to the mutual coexistence of Lewis and Brvinsted acid sites. The Lewis acid sites imparted by active W metal sites adsorb hydrogen proton for catalytic transfer hydrogenation of FUR to FAL, while the predominant Brvinsted acid sites catalyze the hydrolysis of FAL to LA. Consequently, H3PW12O40/SiO2 revealed to be a potential catalyst producing an similar to 51% LA yield under optimized reaction conditions. Moreover, the catalyst was found to be reusable for three catalytic cycles. This study paves the way to develop future biorefinery, particularly direct conversion of FUR to LA over a bifunctional catalyst with a liquid H-donor, in an environmentally benign manner and comply with the green chemistry principles.